REBRANDING USAHA BENGKEL OTOMOTIF MELALUI DESAIN KONTEN INSTAGRAM DAN MEDIA PROMOSI - Halimi, Halimi; Prakoso, Satriya Agung; Rochmaniah, Ainur; Febriana, Poppy (Jurnal Bina Bangsa Ekonomika, 2025)
The workshop business is a competition with high competitiveness with many competitors engaged in vehicle repair services. Fierce competition between automotive workshops encourages more effective, innovative and solution-oriented business branding. The "Jancuk Garage" workshop is a business in the field of motorcycle repair with several advantages but a low customer ratio. The purpose of the rebranding is to introduce Jancuk Garage to the public, increase the customer ratio, increase the positive image of the business in the eyes of the public and build righteousness and reputation. The implementation method includes creating social media content on an attractive Instagram account with the identity of Jancuk Garage's business so that it is known by the wider community. Make brochures, name cards, stickers and boxes of criticism and suggestions to be shared with the public which are effective promotional materials. Build good communication with customers and certain communities and improve good service from handling to facilities at the workshop